Proceedings of the Twelfth International Cryogenic Engineering Conference : Southampton, UK, 12-15 July 1988 : ICEC 12 - Scurlock, R. G. (Ralph Geoffrey); Bailey, C. A. (Butterworth, 1988)
Proceedings of the Twelfth International Cryogenic Engineering Conference Southampton, UK, 12-15 July 1988.